Thermoplastic polyurethane/polypropylene blends based on novel vane extruder: A study of morphology and mechanical properties. Issue 3 (9th July 2013) - Jia, Shikui; Qu, Jinping; Liu, Weifeng; Wu, Chengran; Chen, Rongyuan; Zhai, Shufeng; Huang, Zan
<x xml:space="preserve">Abstract</x> Thermoplastic polyurethane (TPU) polypropylene (PP) blends of different weight ratios were prepared with a self‐made vane extruder (VE), which generates global dynamic elongational flow, and a traditional twin‐screw extruder (TSE), which generates shear flow. The mechanical properties, phase morphology, thermal behavior, and spherulite size of the blends were investigated to compare the different processing techniques. Samples prepared with a VE had superior mechanical properties than the samples prepared with a TSE. Scanning emission micrographs show that the fiber morphology of the TPU/PP blends (<60 wt% TPU) was improved by elongational flow in VE. Differential scanning calorimetry curves indicate that a dynamical elongational flow could improve the miscibility of the TPU/PP blends. The U‐shaped spherulite size curve indicates the changes in the spherulite size, as observed from a polarization microscope. Interlocked spherulites also reveal the apparent partial miscibility of the TPU/PP blends under elongational flow. POLYM. ENG. SCI., 54:716–724, 2014. © 2013 Society of Plastics Engineers